Comportamiento de planchas onduladas de fibrocemento sometidas a cargas de succión - Molina, Julio Cesar [UNESP]; Villas Bôas, Daniel [UNESP]; Negreli, Murilo [UNESP]; Duarte de Souza, Alexandre Jorge [UNESP] (My University, 2018)
This paper presents two numerical models for the evaluation of the distribution of stresses in corrugated sheets of fibre cement subjected to uplift load. The numerical simulations, in this case, were made from three-dimensional models using the software SAP2000Nonlinear, version 7:42, which has as base the finite elements method (MEF). Corrugated sheets with thickness of 5 mm considering two different spans, i.e., 1100 mm and 1530 mm were evaluated. The sheets had the 2nd and 5th high waves fixed. The load of suction applied on the sheets was 10 kN/m2, and it was verified that the stresses on the sheets are distributed heterogeneously in a more complex pattern than for the bending stresses for vertical loads. The sheets suffer bending in transverse and longitudinal directions for the suction load applied, and the attachment points of sheets present concentration of stresses. The numerical results of the stresses showed good agreement with the results obtained from other researchers and these results can be used to predict the behavior of corrugated sheets of fibre cement subjected to wind load suction.
Behavior of corrugated fibre cement sheets subjected to suction loads
Keywords: Fibre cement; Numerical simulation; Stresses